RESPON BEBERAPA VARIETAS PADI (Oryza sativa L.) LAHAN PASANG SURUT TERHADAP BERBAGAI TINGGI MUKA AIR TANAH - Hayati, Hayati; Syafrinal, Syafrinal; Ardian, Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this research is to determineÂ  the response of various tidal swamp varieties of paddy rice (Oryza sativa L.) on various ground water levels. The experiment was conducted in an experimental field of Faculty of Agriculture, Riau University, from July until December 2016. The experiment was conducted by experiment using completely randomized design (RAL) with two factors, namely rice field varieties, and water table height. Varieties are used: IR-42, Inpari 13 and Bamban Lentik. Height of ground water used 5 cm, 10 centimeter, 15 cm and 20 centimeter. The observed parameters were: plant height, tillers maximum number, number of productive tillers, age of panicles, panicle length, harvest age, percentage of unripe rice per hill, weight of dried grain per clump, and weight of 1000 grain of pithy rice. The results obtained in the analysis using anova and HSD of 5%. The results showed that the responses of IR-42 and Inpari 13 varieties to the 10 cm height of the ground water surface resulted in the age of panicles and the fastest harvest age, and yielded the weight of dry grain per clump, the percentage of unlogged rice per hill and the weight of 1000 rice grains. Response of Bamban Lentik varieties to 20 cm high water levels showed the age of panicles and the fastest harvest age, and yielded the weight of dry grain per hill per hill, the percentage of pithy rice per hill and weight of 1000 grain of the highest pine rice.Keywords: Water level, varieties, rice